STUDI PERBEDAAN ANTARA PRESTASI BELAJAR MANDIRI DENGAN BELAJAR PENDAMPINGAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA SISWA TUNA WICARA SMALB - Retno Wati (Academy of Education Journal, 2016)
This study discusses the results of independent learning by assisting learning in PKB subjects specifically students of speech class XI SLALB SLB Negeri 2 Bantul. Total population of 7 students with census techniques, the population used as research. From the analysis results obtained t count of 13.28 while t table at a significance level of 5% of 2.26. With t arithmetic> t table there is a difference in independent learning achievement with Mentoring learning. Thus the hypothesis "It is suspected that the learning achievement of students who are mentoring is better than the learning achievement of students who are self-learning in Civics subjects in speech impaired students of class XI SLALB SLB Negeri 2 Bantul 2016/2017 Academic Year".